The Effect of Muicle–Chitosan Edible Coatings on the Physical, Chemical, and Microbiological Quality of Cazon Fish (Mustelus lunulatus) Fillets Stored in Ice - José Alberto Cruz-Guzmán; Alba Mery Garzón-García; Saúl Ruíz-Cruz; Enrique Márquez-Ríos; Santiago Valdez-Hurtado; Gerardo Trinidad Paredes-Quijada; José Carlos Rodríguez-Figueroa; María Irene Silvas-García; Nathaly Montoya-Camacho; Victor Manuel Ocaño-Higuera; Dalila Fernanda Canizales-Rodríguez; Edgar Iván Jiménez-Ruíz (Foods)
Fishery products are highly perishable; therefore, effective preservation strategies are essential to maintain their freshness, quality, and shelf life. One promising approach involves the use of edible coatings formulated with natural extracts, such as muicle (Justicia spicigera). This study evaluated the effect of a muicle–chitosan edible coating on the physical, chemical, and microbiological quality of cazon fish (Mustelus lunulatus) fillets stored in ice for 18 days. The muicle extract was obtained by macerating dried leaves for 48 h, and its antibacterial activity was subsequently assessed. A control group (C) and three treatments—muicle extract (ME), chitosan (CH), and a combined muicle–chitosan coating (MECH)—were applied and monitored throughout the storage period. Quality parameters, including pH, colour, water-holding capacity (WHC), texture, total volatile basic nitrogen (TVB-N), and mesophilic microbial counts, were evaluated. The muicle extract exhibited antibacterial activity, with MIC and IC50 values of 3.01 ± 0.73 and 204.56 ± 20.23 µg/mL against Shewanella putrefaciens, and 0.10 ± 0.07 and 118.09 ± 14.51 µg/mL against Listeria monocytogenes, respectively. Treatments of ME, CH, and MECH significantly improved (p < 0.05) the quality of fillets by reducing TVB-N, pH, and microbial load compared to the control. In conclusion, the muicle extract demonstrated antibacterial potential and, either alone or in combination with chitosan, effectively preserved the physical, chemical, and microbiological quality of cazon fillets during ice storage.